Feasibility of multimedia animations as preoperative guides for urgent abdominal surgeries in a public hospital in Brazil. Issue 5 (19th September 2022) - Schnitman, Gabriel; Gomes, Danila; Deckelbaum, Dan; Utiyama, Edivaldo Massazo
Abstract: Health literacy, culture and language play vital roles in patients' understanding of health issues. Obstacles are more evident in low- and middle-income countries (LMICs), where inadequate patient education levels are higher and hospital resources are lower. This is a prospective pilot study assessing the feasibility of digital preoperative animations as guides for surgical patients. Patients admitted to a public hospital in Brazil for acute cholecystitis or appendicitis were included. Feasibility was represented by acceptability rate and ease of integration with department protocols. Thirty-four patients were included, and 26 patients concluded the intervention (76.5% acceptability rate). Demographic factors seemed to affect the results, indicated by higher acceptability from those with lower education levels, from younger patients and from women. Few studies have evaluated the use of multimedia resources for surgical patients, and no studies assessed the use of animations as digital patient education resources in an LMIC. This study demonstrated that the use of animations for patient education in LMICs is feasible. A step-based approach is proposed to aid the implementation of patient education digital interventions. The use of digital multimedia animations as preoperative guides in LMICs is feasible. It may help improve patient education and promote clinical benefits.